Nursing care in the face of autistic disorder: Integrative review (Research, Society and Development, 2022)
Autistic Spectrum Disorder (ASD) is characterized by a syndrome that interferes with neurodevelopment, thus hindering cognition, language, behavior, and social interaction. The aim of this study was to identify the nursing care provided to Autistic Spectrum Disorder patients and their caregivers. This is an integrative literature review, carried out from February to May 2022, in the LILACS, MEDLINE, BDENF, and SCIELO databases via BVS. Fourteen articles were selected for the final sample. After the analysis of the articles selected to compose the results, it was identified that nursing has become the main and indispensable element for assistance in the face of the autistic disorder. We conclude that the role of nursing is fundamental in this process, since it is the first professional to have contact with the child, following its growth and development.